2015
DOI: 10.1152/ajpendo.00180.2015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase control of 4E-BP1 phosphorylation state is central for glycolytic regulation of retinal protein synthesis

Abstract: Gardner TW, Abcouwer SF, Losiewicz MK, Fort PE. Phosphatase control of 4E-BP1 phosphorylation state is central for glycolytic regulation of retinal protein synthesis. Am J Physiol Endocrinol Metab 309: E546 -E556, 2015. First published July 21, 2015; doi:10.1152/ajpendo.00180.2015.-Control of protein synthesis in insulin-responsive tissues has been well characterized, but relatively little is known about how this process is regulated in nervous tissues. The retina exhibits a relatively high protein synthesis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
(63 reference statements)
0
13
1
Order By: Relevance
“…Glycolysis is considered as a "central" carbon metabolic pathway because it is the backbone of several metabolic pathways and is pivotal for energy homeostasis (Akram, 2014;Dashty, 2013;Kornberg, 2000). On the other hand, 2-DG may markedly inhibit glycolysis that is essential for viral replication (Gardner, Abcouwer, Losiewicz, & Fort, 2015;Maus et al, 2006;Muaddi et al, 2010). This observation highlights the notion that HBV replication requires glycolysis in host cells.…”
Section: Discussionmentioning
confidence: 91%
“…Glycolysis is considered as a "central" carbon metabolic pathway because it is the backbone of several metabolic pathways and is pivotal for energy homeostasis (Akram, 2014;Dashty, 2013;Kornberg, 2000). On the other hand, 2-DG may markedly inhibit glycolysis that is essential for viral replication (Gardner, Abcouwer, Losiewicz, & Fort, 2015;Maus et al, 2006;Muaddi et al, 2010). This observation highlights the notion that HBV replication requires glycolysis in host cells.…”
Section: Discussionmentioning
confidence: 91%
“…7B). Conversely, mTOR, p-mTOR and their downstream targets were upregulated in the knockout mice, including pS6, glucose transporter 1 (GLUT1) and phosphorylated 4E binding protein-1 (p4EBP1), which promotes protein synthesis (25,26). Conversely, no difference in expression was found in unphosphorylated S6 and 4EBP1 in the Tsc1 loxP/loxP Pde6b H620Q/ H620Q versus the Tsc1 -/-Pde6b H620Q/H620Q mice.…”
Section: Downstream Targets Of Mtor Were Upregulated Inmentioning
confidence: 99%
“…Thus, inhibitory FGF signaling in chondrocytes stimulated PP2A activity without any effect on mTORC1 activity [51]. Similarly, in insulin stimulated rat retinas treated with a glycolytic inhibitor, 4E-BP was rapidly dephosphorylated with no reduction in mTORC1 activity detected [54]. The cases like these can serve as experimental models to digest the mechanism of PP2A activation.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner et al reported that 4E-BP is rapidly dephosphorylated in the presence of glycolytic inhibitor in ex vivo rat retinas stimulated with insulin [54]. This dephosphorylation was mostly prevented by either 1µ M OA (PP1/PP2A inhibition) or by cadmium (PPM1 inhibition) suggesting that more than one phosphatase might be involved in dephosphorylation of all four residues, or maybe, 4E-BP phosphatase has to be activated (directly or not) by another phosphatase.…”
Section: Regulation Of Eif4f Activity By Ser/the Phosphatasesmentioning
confidence: 99%